2002
DOI: 10.1007/s00497-002-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pollen growth transition in self-incompatible Petunia inflata

Abstract: In Petunia inflata, as in other species that shed bicellular pollen, early pollen tube growth in the pistil is slow, then increases 2-to 5-fold depending on the genotype of the female parent. We refer to the time point at which pollen tubes enter the accelerated phase of growth as the pollen growth transition (PGT). Here, we present evidence that pre-PGT and post-PGT growth are quantitatively and qualitatively different, and that the PGT is triggered when pollen tubes reach the transition zone (TZ) below the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…We found that N. odorata tubes had significantly thicker walls than did B. schreberi . Wall thickness plays a role in resisting turgor pressure (Styles and Singla, 1987; Lubliner et al, 2003; Parre and Geitmann, 2005b), consistent with our finding that tube walls of N. odorata were thinner when growing within semisolid tissue than within secretions.…”
Section: Discussionsupporting
confidence: 89%
“…We found that N. odorata tubes had significantly thicker walls than did B. schreberi . Wall thickness plays a role in resisting turgor pressure (Styles and Singla, 1987; Lubliner et al, 2003; Parre and Geitmann, 2005b), consistent with our finding that tube walls of N. odorata were thinner when growing within semisolid tissue than within secretions.…”
Section: Discussionsupporting
confidence: 89%
“…The positive correlation between style length and the number of pollen grains adhering to the stigma may result in a greater opportunity for selection among male gametophytes in flowers with relatively long styles. Large pollen loads may result in higher rates of pollen germination success than small ones (e.g., Brewbaker and Majumder, 1961), and subsequent selection among male gametophytes may be particularly strong as pollen tubes grow from the stigma to the upper style (Erbar, 2003; Lubliner et al, 2003; Stephenson et al, 2003). Consequently, plants with relatively long styles could benefit if receiving more pollen increases seed quality by increasing selection against poor quality male gametophytes during pollen germination and penetration of the stigma.…”
Section: Discussionmentioning
confidence: 99%
“…There is biphasic growth of conspecific pollen tubes in the pistils of Petunia , with a pronounced acceleration of the growth rate by 12 h post-pollination [25]. Biphasic pollen tube growth is seen in P. axillaris pistils after conspecific pollination, but P. exserta pollen also performs well in P. axillaris pistils and their pollen tubes display the same pattern of biphasic growth as conspecific pollen tubes (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The heterospefic pollen continues to grow slowly for at least 72 h, by which time pollinated flowers start to exhibit floral senescence. Seed set fails in this interspecific pollination presumably because the pollen tube growth transition [25] fails to occur. The dynamics of heterospecific pollen tube growth are consistent with incongruity between P. axillaris pistils and P. integrifolia pollen, and it appears to be the underlying cause of the reproductive barrier between the two species when the former is the pistillate partner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation